(untitled) (The Review of Diabetic Studies, 2025)
Background: Immunotherapy has shown transformative efficacy in mismatch repair-deficient (dMMR) or microsatellite instability-high (MSI-H) subtypes of colorectal cancer (CRC), which is a major global health burden. However, most patients have microsatellite-stable (MSS) or mismatch repair-proficient (pMMR) disease, where the benefits of immunotherapy are still limited. Current data on immunotherapy results across various CRC populations and treatment settings is compiled in this systematic review. Methods: In accordance with PRISMA standards, we carried out a systematic review by searching for articles published between 2000 and 2025 in Cochrane CENTRAL, PubMed Central, and Web of Science. Two Phase III randomized controlled trials (RCTs), five Phase II single-arm trials, and one retrospective cohort study were among the eight studies that satisfied the inclusion criteria. ROB-2 for RCTs and ROBINS-I for cohort studies were used to evaluate the risk of bias. Study design, sample characteristics, interventions, efficacy outcomes (overall survival, progression-free survival, objective response rate, disease control rate), and safety profiles were all included in the data extraction process. Results: Among 1,371 patients, MSI-H/dMMR metastatic CRC showed strong responses to immune checkpoint inhibitors, with objective response rates ranging from 43.8% to 50% and median progression-free survival ranging from 16.5 months (pembrolizumab) to not reached (nivolumab plus relatlimab). In cases of localized dMMR illness, neoadjuvant immunotherapy showed pathologic complete response rates ranging from 44% to 68%. On the other hand, MSS populations had worse outcomes than normal salvage therapy with a median overall survival of 10.9 months in refractory situations. Immunotherapy had better safety ratings than chemotherapy, with 10% to 23% of patients experiencing grade 3 or greater treatment-related side events versus 48% to 66% with chemotherapy. Conclusion: immunotherapy provides significant therapeutic benefit in MSI-H/dMMR CRC across treatment lines and contexts, with positive safety and long-lasting responses. The low efficacy in MSS populations highlights the necessity for combined techniques and biomarker-driven patient selection to increase the benefits of immunotherapy.